2011
DOI: 10.1021/cs200058q
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Scanning Transmission Electron Microscopy Investigations on a MCM-41 Supported Cluster Derived Enantioselective Ruthenium Nanocatalyst

Abstract: The asymmetric hydrogenation of methyl pyruvate to methyl lactate, by cinchonidium functionalized MCM-41 supported [Ru4(μ-H)3(CO)12]− as the precatalyst has been studied kinetically and by scanning transmission electron microscopy (STEM). Existence of an induction time and two competitive equilibriums are inferred from the time monitored conversion data. Steady state approximation gives a poor fit, but a kinetic model (Eley−Rideal) consisting of a fast equilibrium between methyl pyruvate and the catalyst, a sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
6
1
Order By: Relevance
“…In nanocatalysis, the dependence of selectivity of a given reaction on specific crystal planes, particle size, and nature of the stabilizer is well established 8. 3537 We are unable to record high‐angle annular dark field scanning TEM data of 3 ; however, as mentioned earlier, HRTEM images show nearly monodisperse crystalline particles with predominantly Ru(1 1 1) crystal planes (Figure 1).…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…In nanocatalysis, the dependence of selectivity of a given reaction on specific crystal planes, particle size, and nature of the stabilizer is well established 8. 3537 We are unable to record high‐angle annular dark field scanning TEM data of 3 ; however, as mentioned earlier, HRTEM images show nearly monodisperse crystalline particles with predominantly Ru(1 1 1) crystal planes (Figure 1).…”
Section: Resultsmentioning
confidence: 78%
“…Various techniques such as extended X‐ray absorption fine structure have shown that in inorganic oxide‐supported carbonyl cluster‐derived nanocatalysts, the essential integrity of the original polyhedral structure is retained in the decarbonylated form 33. By using high‐angle annular dark‐field scanning TEM and kinetic analyses, we showed that on functionalized MCM‐41‐supported [H 3 Ru 4 (CO) 12 ] − ‐derived nanoparticles, the tetrahedral Ru 4 framework is retained 8. There is enough evidence to show that in solution, subnanometer Rh 4 clusters with partial coordinative unsaturation are relatively robust catalysts.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In this reaction, the catalyst systems are mainly developed on a solid support. Previously, we have reported the enantioselective hydrogenation of ketoester and ketone using [Pt 15 (CO) 30 ] 2− and [H 3 Ru 4 (CO) 12 ] − cluster‐derived supported catalysts modified with functionalized cinchonidine 2124. In this context, asymmetric hydrogenation by non‐supported Pt NPs, especially with Pt NRs as catalyst, is of special interest due to the high activity, selectivity, and large surface area of nanostructured materials.…”
Section: Methodsmentioning
confidence: 99%